Influence of laser beam diameter on the mechanical properties of selective laser melted 316L stainless steel and pure nickel parts - Yan, Jiwei (Nanyang Technological University, 2021)
Selective laser melting (SLM) has opened doors for the efficient fabrication of individually tailored functional parts. It can produce much complicated three-dimensional metal or alloy structure and is widely used in many areas. Among SLM process parameters, laser power and scanning speed are commonly studied to influence material characteristics and build qualities like density and porosity. The laser beam diameter is a parameter that has not been studied as comprehensively. It can be varied by moving the machine's platform to heights above or below the laser's focal plane. By changing the defocus distance, the intensity of the laser changes. The resulting melt pool morphology has been found from keyhole mode to conduction mode melting, and vice versa. Despite identical laser power, scanning speed, hatch spacing, and layer thickness. This variation in melt pool morphology due to different laser beam diameters will also affect selective laser melted parts' mechanical properties. The mechanical properties selective laser melted 316L stainless steel and pure nickel parts printed with varying laser beam diameters were analyzed through a series of characterization techniques such as density, optical microscopy, hardness test, and tensile test. The beam diameter was increased from 44.9µm to 126µm, and the density of stainless steel 316L samples also increased from 96% to 99%. The melt pool width becomes broader and broader, but the depth becomes shallower with increasing in defocus level. However, the melt pool morphology is not obvious for pure nickel sample although it has a density increasing from 94% to 99%. The ultimate tensile strength of selective laser melted stainless steel 316L tensile coupon is 700MPa which is the highest when printed with a 74µm beam diameter, at 1.5mm defocus level. Grain size has a significant increase from 1.5mm defocus level to 3mm defocus level. The grain shape changed from equiaxed to columnar shape as the defocus level increases.